2020
DOI: 10.1002/app.49125
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of flexible ruthenium oxideloaded polyaniline/poly(vinyl alcohol) nanofibers

Abstract: Polyaniline/poly(vinyl alcohol)/ruthenium oxide (RuO2) composite nanofibers were produced by electrospinning technique. Hydrous ruthenium chloride was used as a precursor at different concentrations, and the samples were annealed at 200°C. The morphology of the nanofibers was investigated by scanning electron microscopy. The average diameter of the produced nanofibers is between 200 and 300 nm. Fourier transform infrared spectroscopy and Raman spectroscopy were used for the investigation of the vibration modes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…This was mainly assigned to the increase of the carrier concentration, as well as the growing rate of electron transfer from valence to the conduction band [ 28 ]. At elevated temperatures, sufficient energy was attained by the ions, which empowered them to move and diffuse to the metal electrodes due to their potential differences [ 27 ]. The figure illustrates single semicircles for all measurements, which revealed that a membrane may be presented by a single parallel RC circuit [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was mainly assigned to the increase of the carrier concentration, as well as the growing rate of electron transfer from valence to the conduction band [ 28 ]. At elevated temperatures, sufficient energy was attained by the ions, which empowered them to move and diffuse to the metal electrodes due to their potential differences [ 27 ]. The figure illustrates single semicircles for all measurements, which revealed that a membrane may be presented by a single parallel RC circuit [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…This work represents a continuation of our previous investigations of producing PVA nanoparticle composites for device applications ref. [ 11 , 12 , 15 , 17 , 27 , 28 , 29 , 30 ]. The previous investigations revealed that the modification of PVA with nanoparticles and plasticizers permit fine adjustments of the electrical and mechanical properties of its membranes.…”
Section: Introductionmentioning
confidence: 99%
“…The figures illustrate that the radii of the semicircles decrease with temperature that refers to their negative temperature coefficient of the resistance for the membranes. 15,46 Nevertheless, the resistance value cannot be utilized to compare the different membranes due to their unequal thicknesses. Hence, the resistivity (ρ) is calculated using the thickness of a membrane (l) and contact area (A): ρ ¼ R A l .…”
Section: Resultsmentioning
confidence: 99%
“…The DC resistance of a membrane can be determined by fitting the dependence, where it is referred to as the radius of the semicircle. The figures illustrate that the radii of the semicircles decrease with temperature that refers to their negative temperature coefficient of the resistance for the membranes 15,46 . Nevertheless, the resistance value cannot be utilized to compare the different membranes due to their unequal thicknesses.…”
Section: Resultsmentioning
confidence: 99%
“…Electrospinning is a versatile technique to fabricate uniform ultrafine fibers with diameters ranging from 20 to 2000 nm directly from polymer solutions or melts. 23,24 These porous nanofiber mats prepared by this technique were ideal supporting matrices for palladium catalysts.…”
Section: Introductionmentioning
confidence: 99%